PROACTIVE PUBLICATION OF INFORMATION ABOUT JUDICIAL CASES AND ACTS OF THE COURT OF JUSTICE - Petrova, Mariana; Hristov, Hristo (Administrative and Criminal Justice, 2018)
The integration of IT and Internet technologies in the work of the judiciary institutions has become a major factor in the changes in the administration of justice. On the one hand, technology has become accessible to law enforcement agencies and has become an effective means of carrying out their work and managing document flow. On the other hand, ICTs have been made accessible to citizens and users of the justice system and to electronic reporting provided by the judicial authorities and other online services. The potential of technology is to provide more and more new or improved services in the field of justice, as well as the ability of citizens to actively use them.The publication of court documents and the provision of data on court cases electronically via the Internet affects a wide range of public relations and rights enshrined in national and international regulations.One of the main elements of the legislation on the access to information is the principle that public institutions must follow a policy aimed at publishing information of general interest without filing an application, i.e. Proactive publishing policy.